Utopia and civilisation in the Arab Nahda - Hill, P (2015)
This doctoral thesis explores the contexts of utopian writing and thinking in the Nahda, the Arab 'Awakening' of the long nineteenth century. Utopian forms of social imagination were responses to fundamental changes in the societies of the Arab-Ottoman world brought about by integration into a capitalist world economy and a European-dominated political system. Much Nahda writing was permeated by a sense of a 'New Age' opening and of wide horizons for future change – and this was not simply illusory, but a direct response to actual and massive changes being wrought in the writers' social world. My study focusses on Egypt and Bilād al-Shām in the middle decades of the nineteenth century, from the early 1830s to the mid-1870s. An initial chapter offers a definition of the social classes and groups which contributed to the Nahda in these years – such as the Beiruti bourgeoisie and the Egyptian-Ottoman official class – drawing on the work of Arab Marxists such as Mahdī 'Āmil and social historians such as Bruce Masters. The following chapters deal in detail with writings produced by three distinct cultural formations within the Nahda movement, and with different aspects of their social imagination. Chapter 2 examines the discourse of civilisation (tamaddun) through the work of the Beiruti writers Khalīl al-Khūrī and Buṭrus al-Bustānī in the 1850s and 1860s. Chapter 3 deals with Nahda writers' sense of their place within the European-dominated world, mainly through translations of geography books made by Rifā'a al-Ṭahṭāwī in Mehmed Ali's Egypt in the 1830s and 1840s. Chapter 4 examines the utopian aspirations of the Nahda, through a close study of the major utopian literary work of the period, Fransīs Marrāsh's Ghābat al-Ḥaqq (The Forest of Justice, 1865). Finally, a conclusion places my study in relation to other recent work in the field of 'Nahda studies'.